Designing Classroom Activities for Teaching English to Children - Emma Malia (TEFLIN Journal: A publication on the teaching and learning of English, 2004)
This paper discusses some ideas on activities teachers of young learners make young learners do by way of materials. The paper also gives a number of suggested analyses of selecting or designing an activity to use with young learners. The suggested analyses of the activity deal with goals, input, procedures, outcome, teacher role, learner role and organization. The idea is not only to help young learners understand the language they hear but also to encourage young learners, who developmentally have shorter attention span composed to adults, to learn English naturally.